PENGARUH AIR REBUSAN DAUN KARSEN TERHADAP PENURUNAN KADAR KOLESTEROL PADA LANSIA - Sry Wahyuni Sry Wahyuni; Sumiyati Sumiyati; Masyitah Wahab Masyitah Wahab (Bina Generasi : Jurnal Kesehatan, 2022)
Someone with high risk of blood cholesterol up to 200 mg/dL is having high risk of health problems. And the higher the cholesterol rate, the higher the risk of heart and blood vessels. Kersen leaf dust (m. calabura l.) Saponin lowered cholesterol ingrate and increased in secretion, flavonoid caused a reduction in transfusion HMG-CoA to mevalonat, resulting in cholesterol synthesis decline. The goal of this study is to prove the effects of carsen stew's water on decreasing the cholesterol level of the elderly. This method of research is eskperimental design using a one-group pretest-posttest design model, it USES 10 old samples that have cholesterol levels above 200 mg/ dl and are willing to be cited for respondents with samples of a sampling exercise. Data gained from cholesterol levels before and after an intervention on the observation sheet using normal distribution saphiro wilk test has a p-value > 0.05. The normality test using the partner t test acquired data with the grade of p-value = 0.030 < 0.050 this indicates ho is rejected, thus assessing a different cholesterol level before and after the water treatment of carsen leaves against cholesterol sufferers.